Kepimpinan Islam: Satu Agenda Pembangunan Ummah - Muhammad, Shukeri (Jurnal Usuluddin, 1997)
Islamic Leaderships is the agent of change in ummah. Emphasis is given to the missions, objectives and conditions of the Islamic- Leaderships